The evolution of process safety standards and legislation following landmark events—what have we learnt?. Issue 2 (3rd August 2015) - Kerin, Trish
Abstract : While modern process safety can be dated back to E.I. duPont in the early 1800s with the building of black powder plants including separation distances, and blast zones, the management of process safety has come a long way. Despite this, however, we have continued to see many catastrophic incidents occur, across a range of industries. There have been significant learning opportunities from the catastrophes, but are we actually applying the learnings? Exploring the past 40 years history shows a number of landmark process safety events. These events have not only changed our state of knowledge for managing process safety but have also resulted in standards and legislative change in multiple jurisdictions. This article explores the significant learnings that came out of the various landmark process safety events and the impact these changes have had on how process safety is managed today. Incidents considered as case studies in this article include the following: Flixborough UK (1974), Seveso Italy (1976), Bhopal India (1984), Piper Alpha UK (1988), Longford Australia (1998), Texas City Refinery USA (2005), Montara Australia (2009), Macondo USA (2010), and Pike River New Zealand (2010). © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 165–170, 2016